Effects of CeO2 Nanoparticles on Nutritional Quality of Two Crop Plants, Corn (Zea mays L.) and Soybean (Glycine max L.) - Xin Gui; Chaonan Dong; Shixian Fan; Chunlei Jiao; Zhuda Song; Jiaqi Shen; Yong Zhao; Xuanzhen Li; Fawen Zhang; Yuhui Ma; Xiao He; Aijun Lin; et al. (Molecules, 2023)
With the widespread applications of manufactured nanoparticles (NPs), there are increasing concerns about their potential adverse effects on the environment and living systems. Many studies demonstrated that NPs could significantly affect the growth and development of crop plants. However, knowledge regarding the impacts of NPs on crop quality is rather limited. In this study, the effects of CeO2 NPs (25, 75, and 225 mg Ce/kg) and CeCl3 (25 mg Ce/kg) on the nutritional components of soil-cultivated corn and soybean plants were evaluated. Both treatments tended to decrease the dry weight of grain per plant, while only 225 mg/kg CeO2 NPs on soybean and CeCl3 on corn showed statistical significance compared with the respective control. CeO2 NPs at 225 mg/kg significantly decreased the content of starch in the corn kernels by 18.2% but increased total phenols in soybean seeds by 18.4%. Neither CeO2 NPs nor CeCl3 significantly affected the contents of minerals in corn kernels except for Zn. However, in the case of soybean, the two treatments tended to decrease the contents of P, Zn, Mn, and Mo but increase the content of S. Overall, the results suggest that CeO2 NPs and Ce3+ ions showed similar but not identical effects on corn and soybean plants. CeO2 NPs affect the nutritional quality of crop plants in a species-dependent manner.